Advertisement content in the Iraqi satellite channels and their commitment to advertisement ethics. - Salman Shafae, Abdulmohsin (ALBAHITH ALALAMI, 2025)
The problem of the study is to monitor the content presented in the Iraqi satellite channels to identify the nature of the ideas contained in these ads and to identify the values ​​carried by the creative strategies and ad campaigns that use. Where the satellite is one of the most important technological developments in the field of communications in the nineties and the ads in various forms and functions one of the contents provided by satellite channels where these channels are keen to direct their messages in particular and communication, in general, to address a certain audience and convince and influence in order to achieve certain purposes of the source Or the body from which it originates, especially those that result in an increase in their material returns by relying somewhat on commercial advertising in support and financing of a particular channel. The study uses the methodology of the media survey. This study belongs to the field of descriptive studies, which aims to describe the situations, phenomena, and events and to collect accurate facts about them. Through an analytical study of the advertising content on the eastern channel of Iraq, the sample of the analytical study was withdrawn from 15/7/2018 to 15/10/2018 In order to identify the nature of the ad content submitted and analyzed 58 ads, the results of the study showed the diversity and diversity of ethical violations, the multiplicity, and diversity of negative values ​​reflected by the ads on the Eastern channel has been hatred and hatred at the top of these negative values, The most widely used in the advertisements submitted to the Iraqi Sharqiya.